THE ROLE OF THE HEAD OF FINANCIAL AFFAIRS IN THE MANAGEMENT OF THE VILLAGE FINANCIAL SYSTEM IN BUNGA VILLAGE, BONE RAYA DISTRICT, BONE BOLANGO REGENCY - Agrista Tueno; Darman; Harsono Ahmad (Journal of Economic, Business, and Administration (JEBA), 2026)
The implementation of digital financial systems is a critical determinant for enhancing local accountability, yet it is often constrained by structural, technical, and human resource gaps within village administrations. This study aims to determine and analyze: (1) how the Head of the Financial Division (Kaur Keuangan) executes their treasury roles and functions within the Village Financial System (SISKEUDES) framework, and (2) the technical, competence-based, and coordination challenges encountered during its execution. Conducted in Bunga Village, Bone Raya Sub-district, Bone Bolango Regency, this study adopted a qualitative descriptive design. Data were collected through field observations, passive documentation, and semi-structured, in-depth interviews using a purposive sampling technique with two key informants: the Head of Bunga Village (as the PKPKD) and the Village Secretary (as the PPKD coordinator). The gathered data were evaluated using the interactive analysis model of Miles, Huberman, and Saldaña, and validated through source and technical triangulation. The results indicate that: (1) the Head of the Financial Division acts as the strategic primary operator of SISKEUDES, successfully transforming manual bookkeeping into an orderly, systematic practice by integrating datasets across seven critical fiscal phases from planning to reporting; (2) the execution remains suboptimal due to a multi-dimensional bottleneck consisting of a lack of Task-Technology Fit (TTF) caused by software errors as a technical barrier, low digital literacy without regular capacity building as a competence barrier, and delayed submissions of expenditure plans (SPP) by section heads (Kasi) as a horizontal coordination barrier; and (3) overcoming this highly inefficient operational loop requires an integrated governance framework where the Village Head strictly enforces data deadlines on activity managers, backed by the continuous oversight of the Village Secretary to secure a transparent digital financial ecosystem.